Improvement keys of advanced encryption standard (AES) Rijndael_M - Shakir M.; Bit Abubakar A.; Bin Yousoff Y.; Sheker M. (Asian Research Publishing Network, 2023)
Rijndael is a specification for the encryption of electronic data that considered as a collection of ciphers with distinct block and key sizes. This study aims to develop the key of Rijndael cipher in order to enhance the level of confusion and diffusion. The tools of analysis, design, implementation, testing, and evaluation have been applied by using the model of software system development life cycle (SDLC). The results of the study show that adding keys to the Rijndael will increase its security level and promote widely use in the organizations. 2005 - 2016 JATIT & LLS. All rights reserved.